The extend of investor relations information's in the Malaysian companies web site - Abdul Hamid, Fathilatul Zakimi; Md. Salleh, Md. Suhaimi; Saad, Sazali (Universiti Utara Malaysia, 2004)
The Introduction and the internet in recent years has provides an interesting alternative for the dissemination and communication of accounting information. Furthermore, the rapidly growing demand for information from investor, corporation in USA and Europe are using internet for their investor communication. The main objective of this study is to extend the prior research in Investor relations by looking to the variation of investor information through Malaysian corporate web site to the factors thought to influence the disclosure. The study revealed that company size and industry classification was found significantly positive association with the existence of investor information in the corporate web site. While for profitability and foreign ownership variables, result show insignificant relationship. The result confirms that companies in Malaysia may not take the opportunity to actually communicate with stakeholders via. Internet, instead choosing to present traditional communication as required by law. Furthermore, Malaysian companies rely on traditional IR communications with institutional investors and funds managers - and this group of investors is usually already well informed about how these firms operate.